School Counselor Supervision in Kentucky A Contradiction in Terms? - Carone, Stacia (Distributed by ERIC Clearinghouse, 1998)
This exploratory study gathered data regarding the supervision of school counselors across the state of Kentucky to find out the nature of supervision being provided to school counselors and the ratio of students to counselors from a representative sample across the state's eight service regions. Superintendents (N=100) were contacted by telephone and asked to report the supervision structure and student-counselor ratios for their districts. Descriptive statistical data is reported. Data collected revealed that many of the school counselors who were questioned were being supervised by administrative professionals, such as principals, who are not required to have training in counseling theories and techniques. In addition, many of the school districts have less than ideal student-counselor ratios. The results imply that school counselors are lacking in specific counseling-related supervision for the primary services they provide. Student-counselor ratios are so high that it is unrealistic to think that school counselors are providing an adequate amount of direct counseling services for which they were hired to perform. Suggestions for future research and implications for school counselors are discussed. (EMK)